Heads and Tails: Studies of Web Search with Common and Rare Queries - Downey, Doug; Dumais, Susan; Horvitz, Eric (SIGIR 2007 (poster), 2007)
A large fraction of queries submitted to Web search engines occur very infrequently. We describe search log studies aimed at elucidating behaviors associated with rare and common queries. We present several analyses and discuss research directions.